First Step to empowering change: enhancing self-efficacy, energy management, and physical activity in patients with sleep apnea - Johannesen, Gitte; Damlund, Anders Ravnholt Schüsler; Grundtvig Vinter, Sofie; Spuur, Helle Skadborg; Sarkez-Knudsen, Mathias; Thomsen, Thora Grothe (Frontiers in Rehabilitation Sciences, 2024)
IntroductionFatigue often leads to a sedentary lifestyle, negatively impacting health, mortality, and quality of life. Engaging in physical activity can be challenging for individuals experiencing fatigue, particularly those with sleep apnea. This study's objective was to assess the “First Step” concepts’ usability in constructing and implementing different interventions through qualitative data. The intervention targets patients with sleep apnea, focusing on individualized energy distribution and meaningful engagement in physical activity.MethodsTwo programs were developed based on the First Step concept, a rehabilitation program and a patient education program. Initially, 13 patients were recruited, split between the groups, with two dropping out. Primarily evaluated through qualitative data, patients in both groups attended group interviews. For one of the programs supplementary quantitative data were collected through the 6-min walk test (6MWT), Sit-to-Stand test, and Canadian Occupational Performance Measure (COPM). Patients in the rehabilitation program also monitored daily step counts using activity trackers.ResultsPatients found the energy management education enlightening, enabling them to make conscious changes in their daily lives. They reported the program's positive reception, with social interaction playing a crucial role in its success. Of the six patients who completed the rehabilitation program, significant improvements in 6MWT scores were observed, indicating enhanced walking endurance. While no changes were seen in the Sit-to-Stand test, COPM results showed notable improvements in performance and satisfaction with chosen activities.DiscussionThe incorporation of the First Step concept empowered patients with sleep apnea to manage fatigue, conserve energy, engage in meaningful activities, and improve their wellbeing. Merging occupational therapy and physiotherapy interventions effectively addressed daily challenges while promoting physical activity. Adaptations to the program, guided by patient feedback, suggest a preference for longer, more personalized sessions. This approach offers a promising pathway to improving quality of life for individuals with chronic conditions.ConclusionOur study highlights the usability of the First Step concept, integrating occupational therapy and physiotherapy, to address challenges in individuals with sleep apnea. The tailored, multidisciplinary intervention prioritizes meaningful activities, focuses on energy distribution and physical exercise, yielding improved satisfaction and performance. Further research is warranted to enhance this salutogenic approach for chronic conditions.